A clinical case of pulmonary form of mucormycosis in a child with acute lymphoblastic leukemia - Yu. Yu. Kozel; O. Yu. Kutsevalova; V. V. Dmitrieva; O. V. Kozyuk; L. B. Kushtova; A. Kh. Khaspekyan; K. S. Aslanyan (Южно-Российский онкологический журнал, 2021)
Mucormycosis of the lungs is a severe infectious complication in patients with acute lymphoblastic leukemia, which develops at the stage of high-dose cytostatic therapy. It is characterized by an extremely aggressive, rapidly progressive course and, without specific treatment, is fatal in a short time. Reliable verification of mucor is necessary due to its resistance to the most commonly used antifungal drugs, particularly to voriconazole.The article presents a clinical case of pulmonary mucormycosis in a 12‑year-old child at the stage of diagnosis of acute lymphoblastic leukemia. The first symptoms of the disease (headaches, malaise and weakness, pallor), changes in the general blood count (hyperleukocytosis up to 200 thousand cells/μl, single platelets). Based on the results of the examination, the main diagnosis was verified for acute lymphoblastic leukemia L2, IFT T-II, CD1a-. At the stage of diagnosis of acute lymphoblastic leukemia, the underlying disease was complicated by the development of right-sided pneumonia according to X-ray examination. To verify the etiology of infiltration of lung tissue, broncho-alveolar lavage was directed to microbiological diagnostics, which included studies: enzyme immunoassay, microscopic and cultural. On the aggregate of all the results obtained, invasive mucormycosis was diagnosed and antifungal therapy was started immediately.